Upotreba formalnih i neformalnih procedura procene u specijalnoj edukaciji i rehabilitaciji – percepcija stručnjaka i studenata - Uzelac, Jovana; Đurašinović, Milica; Glamočak, Sandra; Ivezić, Staša (Specijalna edukacija i rehabilitacija, 2025)
Introduction. Assessment in special education and rehabilitation is a very important and continuous process involving gathering information to decide on further work procedures. Formal and informal assessment procedures are used in this process depending on the needs. Aim. The aim of the research is to determine whether there is a difference in the selection of procedures between the experts and students. Methods. The sample consisted of 181 respondents, of which 87 experts, 31 speech therapists, and 56 special educators. Out of 94 students examined, 61 attended the speech therapy program, and 33 attended the multiple disabilities program. The respondents’ average age was 25.54 years. Data collection was carried out using two online surveys, one of which was intended for experts and the other one for students. The surveys consisted of 19 questions, divided into five areas: general data on the person completing the survey, general information on the reason and usefulness of the assessment, organizing assessment, selection of assessment instruments and application of assessment in practice. Results. The largest number of experts, as well as students, opt for the use of informal assessment procedures. Speech therapists, however, prefer to choose formal procedures, while special educators more often rely on informal procedures. Most students in the speech therapy program prefer to use formal evaluation procedures in their future work, which is opposite to the preferences of students in the multiple disabilities program. Conclusion. Based on the results obtained by this research, it was concluded that informal assessment procedures are the most common choice among both target groups, which shows the recognition of the importance of this type of assessment, but also that professional guidance plays a major role in the selection of the procedures themselves.
Keywords: assessment; formal procedures; informal procedures; experts; students